Investigating demotivation factors of esp learners during covid-19 pandemic: A mixed-method study - Adara, Reza Anggriyashati; Farid, Achmad (Universitas Muhammadiyah Sidoarjo, 2022)
Demotivation factors of ESP students need to be analyzed so that teachers and researchers can provide better approaches to teach them, especially during trying times such as Covid-19 pandemic. Thus, the present study aims to analyze demotivation factors of a group of ESP learners during Covid-19 pandemic. In order to obtain its data, the present study applies a sequential explanatory method. A set of questionnaires were distributed to 48 respondents and semi-structured interviews were conducted to five respondents. The results show that the most salient factors which demotivate the respondents are teachers’ competence and teaching styles as well as inadequate school facilities. On the other hand, lack of intrinsic motivation is shown to be the least salient demotivation factor. The results of present study suggest that the respondents seemed to be demotivated because teaching styles and learning materials are perceived as unsuitable for their needs to improve their English skills and future careers as engineers. In addition, online learning was perceived by the respondents as less ideals to teach English despite their intrinsic motivation to learn English for their personal as well as career gains in the future. Possible solutions are also discussed in the present study. HIGHLIGHTS: Lack of intrinsic motivation is seen as the least demotivating factor. Demotivation factors among ESP learners need to be investigated because they would provide more information to improve learners’ motivation. The present study shows unsuitable teaching styles and materials can lead to students’ demotivation. Conducting needs analysis seems imperative to provide a better teaching approach as well as materials for ESP students.